Legal and institutional aspects of the international monetary system : selected essays - Gold, Joseph; Evensen, Jane B.; Oh, Jai Keun. (Washington : International Monetary Fund, 1984)
This is a collection of the selected essays of the author which is aimed at illuminating an aspect of international monetary law and International Monetary System.
Includes index
Includes bibliographies references.
usc 26/04/18
Loans
Keywords: Money; Money--Law and legislation; International Monetary Fund; Balance of payments; International finance